2018
DOI: 10.1002/chem.201705335
|View full text |Cite
|
Sign up to set email alerts
|

Heterobimetallic Complexes for Theranostic Applications

Abstract: The design of more efficient anticancer drugs requires a deeper understanding of their biodistribution and mechanism of action. Cell imaging agents could help to gain insight into biological processes and, consequently, the best strategy for attaining suitable scaffolds in which both biological and imaging properties are maximized. A new concept arises in this field that is the combination of two metal fragments as collaborative partners to provide the precise emissive properties to visualize the cell as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 97 publications
1
53
0
1
Order By: Relevance
“…Surprisingly, although (diimine)Re I tris‐carbonyl complexes are known to be emissive and are often used as luminescent probes, as reported, for instance, for Au I /Re I heterobimetallic systems, all Pt II /Re I heterobimetallic complexes appear to be nonemissive. This quenching may be explained by the heavy‐atom effect, due to the proximity of the Pt II center to the {(trueNN^ )Re(CO) 3 } fragment.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, although (diimine)Re I tris‐carbonyl complexes are known to be emissive and are often used as luminescent probes, as reported, for instance, for Au I /Re I heterobimetallic systems, all Pt II /Re I heterobimetallic complexes appear to be nonemissive. This quenching may be explained by the heavy‐atom effect, due to the proximity of the Pt II center to the {(trueNN^ )Re(CO) 3 } fragment.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, aurophilic interactions might be beneficial for cell imaging studies due to their often observed fluorescence [11] . In addition, functionalization of the bridge between both NHC moieties of the ligand enables potential sites for bioconjugation and the synthesis of theranostic agents [12] . Recently, Au(I) bridge‐functionalized NHC complexes (e. g. allyl, [13] hydroxyl [8] or carboxylate [9] ) have been reported.…”
Section: Figurementioning
confidence: 99%
“…In recent years heterometallic species have been identified as emerging tools for theranosis . Typically, such compounds are formed by two distinct metallic fragments connected through a linker, where each of the fragments is specifically designed for either cell imaging or therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%